Knowledge and Perceived Effect of Polypharmacy and Potentially Inappropriate Medication Use among Nurses in a Nigerian Tertiary Hospital - Olamide Olajumoke Afolalu; Oluwabusolami Esther Atekoja; Oluwadamilare Akingbade; Karimat Itunu Jolayemi; Zaccheus Opeyemi Oyewumi; Boluwatife Deborah Oyelabi; Semiu Opeyemi Adeyeye (Golestan University of Medical Sciences, 2021)
Background: Polypharmacy (PP) and inappropriate medication use (IMU) are issues that negatively affect the health care system. Despite nurses' engagement and important role in prevention of drug-related issues, awareness regarding consequences of PP and IMU is relatively low. This study aimed to determine the knowledge and perception effects about PP and IMU among nurses in the Lautech teaching hospital, Osun state, Nigeria. Methods: This descriptive, cross-sectional study was performed on 190 randomly selected nurses working at the Lautech teaching hospital (Osun state, Nigeria) in June 2020. Data were collected using a researcher-made questionnaire. The reliability of the questionnaire was verified by obtaining a Cronbach alpha score of 0.77. Data analysis was done in SPSS 25 using descriptive statistics, the Chi-square test. All analyses were carried out at significance level of 0.05. Results: The findings revealed that most nurses (84.2%) had good knowledge about PP. In addition, 93.2% of the nurses claimed that IMU should be entirely avoided. According to the nurses, the most important perceived effect of PP and IMU was adverse drug reactions (57.9%). There was a significant relationship between nurses level of educational and knowledge of PP (χ2=12.095, P=0.002). Moreover, there was a positive correlation between the respondents' age and knowledge of PP (r=0.204, P=0.016). There was also a significant negative correlation between the nurses' knowledge and perceived effect of PP and IMU (r=0.605, P<0.001). Conclusion: The results indicate that the nurses working at the study setting possess good knowledge of PP and IMU. Educational programs such as seminars and workshops are essential for translating this information into routine nursing care.